Whipple Procedure for High-Grade Pediatric Pancreatic Injury After Blunt Trauma: A Case Report - El Gah, David C; Rahayatri, Tri H; Rachmawati, Asri D; Nugroho, Adianto (The New Ropanasuri Journal of Surgery, 2026)
Introduction: Pediatric pancreatic injury isuncommon but carries significant morbidity. While non-operative management is standard for low-grade injuries, the optimal approach for high-grade trauma (AAST grade III–V) remains debated. Pancreaticoduodenectomy (Whipple procedure) is rarely performed due to high procedural risks and is typically reserved for severe pancreatic head injury with concomitant duodenal damage. Case presentations: A 13-year-old boy presented three days after blunt abdominal trauma with epigastric pain and bilious vomiting. CT imaging revealed free fluid, a large retroperitoneal hematoma, and suspected pancreatic head injury. Despite initial stability and conservative management in the High Care Unit, worsening abdominal distension prompted an exploratory laparotomy. Discussion: Surgery revealed pancreatic head laceration and duodenal tears. Consequently, a pancreaticoduodenectomy with pancreaticojejunostomy, choledochojejunostomy, and gastrojejunostomy wasperformed. The patient recovered steadily, resumed oral intake at two weeks, and was discharged in good condition. At the one-year follow-up, he remained asymptomatic and had resumed normal activities. Conclusion. This case demonstrates that pancreaticoduodenectomy is a definitive option for stable pediatric patients with high-grade pancreatic head and duodenal injuries when local reconstruction is unfeasible. However, due to its complexity, it should remain a last-resort strategy reserved for specialized hepatopancreatobiliary centers.